2013
DOI: 10.7314/apjcp.2013.14.2.951
|View full text |Cite
|
Sign up to set email alerts
|

Saffron Reduction of 7,12-Dimethylbenz[a]anthracene-induced Hamster Buccal Pouch Carcinogenesis

Abstract: Our aim was to investigate the chemopreventive potential of saffron in DMBA-induced hamster buccal pouch carcinogenesis. Assessment was by monitoring the percentage of tumor bearing hamsters, tumor size as well as the status of detoxification agents, lipid peroxidation and antioxidants. Oral squamous cell carcinomas were induced in the buccal pouch of Syrian golden hamsters by painting them with 0.5% DMBA in liquid paraffin three times a week for 14 weeks. We observed 100% oral tumor formation with severe hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
10
9
0
Order By: Relevance
“…Furthermore, eroded and ulcerative areas were seen throughout the tumor growth, with spontaneous bleeding. These results are almost the same with that shown by other investigators (21)(22)(23)(24) . Histopathological results of G-B1 showed moderately to poorly differentiated SCC with deeply invading islands of tumor cells into the underlying connective tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, eroded and ulcerative areas were seen throughout the tumor growth, with spontaneous bleeding. These results are almost the same with that shown by other investigators (21)(22)(23)(24) . Histopathological results of G-B1 showed moderately to poorly differentiated SCC with deeply invading islands of tumor cells into the underlying connective tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, eroded and ulcerative areas were seen throughout the tumor growth, with spontaneous bleeding. These results are almost the same with that shown by other investigators (19)(20)(21)(22) . Histopathological results of GII showed moderately to poorly differentiated SCC with deeply invading islands of tumor cells into the underlying connective tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Saffron is a perennial herbaceous plant belonging to the Lily Family within the Lillian's order. Manoharan et al, (2013) described the anti-tumor mechanism of saffron through restoring the detoxifier enzymes, lipid peroxidation suppliers, and antioxidants to the normal level. Tavakkol Afshari et al, (2008) reported IC50 of 800 µg/ml against HeLa and 950 µg/ml against HepG2 cell lines for saffron within 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Saffron is naturally taken from the stigma of the crocus sativus flower (Manoharan et al, 2013). It has been reported that saffron is an antioxidant, anti-cancer, anti-inflammatory, antidepressant, antihistamine, and memory enhancer (Harrington, 2011) and its anti-cancer effects have been confirmed in vitro and in animal models (Zhang et al, 2013).…”
Section: Anti-cancer Effects Of Traditional Medicinal Herbs On Oral Smentioning
confidence: 99%